Pengaruh Model Pembelajaran Two Stay Two Stray (TSTS) dalam Meningkatkan Hasil Belajar Al-Qur’an Hadits Siswa Kelas IV MI Azzein Bogor - Muhammad Zufar; Maemunah Sa’diyah; Retno TriwoelandarI (ALSYS, 2025)
This study is motivated by the low learning outcomes in the Al-Qur’an Hadits subject at MI Azzein Bogor, as well as the suboptimal use of instructional models that enhance student participation and comprehension. The objective of the study is to examine the effect of the Two Stay Two Stray (TSTS) cooperative learning model on improving the Al-Qur’an Hadits learning outcomes of fourth-grade students. A quantitative approach with a quasi-experimental design was employed, involving 50 students divided into two classes: the experimental class (IV-A) and the control class (IV-B), each comprising 25 students. Data were collected through a 30-item multiple-choice test administered as both pretest and posttest. The analysis showed a significant improvement in the experimental class, with the average pretest score increasing from 79.79 to 87.20 in the posttest, and a p-value of 0.00023 (< 0.05). In contrast, the control class, which used conventional teaching methods, showed an insignificant improvement, with the average score rising from 74.56 to 77.76 and a p-value of 0.137 (> 0.05). These findings indicate that the TSTS model has a positive and significant impact on students’ learning outcomes. The main conclusion of this research is that the application of the Two Stay Two Stray learning model is effective in enhancing student achievement in Al-Qur’an Hadits. The study recommends that teachers adopt the TSTS model as a cooperative learning alternative capable of improving conceptual understanding, learning engagement, and students’ social character through interactive and collaborative classroom practices.